Job Loss or Income Loss: How the Detrimental Effect of Unemployment on Men's Life Satisfaction Differs by Immigration Status - Shen, Jing; Kogan, Irena (Frontiers in Sociology, 2020)
Driven by the ongoing debate of job loss versus income loss in understanding costs of unemployment, this study examines how perceptions of unemployment differ between immigrant and native-born men, which in turn, gives rise to the immigrant-native gap in life satisfaction. Based on a countrywide longitudinal dataset in the UK, findings show that immigrant men’s life satisfaction suffers more from the detrimental effect of job loss per se, whereas that of native-born men suffers more in the pecuniary respect, which is mainly driven by perceived financial strain, instead of objective income loss. We speculate that immigrants’ perceptions of unemployment may vary with their durations of residence in the host country, with well-established immigrants perceiving unemployment in the way similar to their native-born counterparts. We test this speculation by focusing only on the immigrant subsample. Findings show that life satisfaction of recent immigrants suffers more from job loss per se, whereas that of established immigrants is affected more by perceived financial strain.